Hypopharyngeal paraganglioma: Case report and review of the literature12. Issue 7 (21st August 2012) - Mehta, Vikas; Fischer, Tova; Levi, Gabe; Wang, Beverly; Urken, Mark L.; Chen, Amy
Abstract Background Paragangliomas are rare, vascular, and predominantly benign neoplasms of neural crest origin. They typically arise in the head and neck from the carotid body, jugulotympanic, or vagal paraganglia. Rarely, paragangliomas occur in the larynx. Only 2 cases of hypopharyngeal paraganglioma have been reported. We discuss the case of a hypopharyngeal paraganglioma and review the literature concerning laryngopharyngeal paragangliomas. Methods and Results We present the case of a woman with 2 months of dysphagia and hoarseness that was found to have a hypopharyngeal paraganglioma. The patient underwent embolization and resection of the mass via a lateral thyrotomy approach. Pathologic analysis and selective staining confirmed the presence of a paraganglioma. Conclusions Proper histopathologic identification of these tumors is tantamount to guiding treatment. The preferred operative approach is a lateral thyrotomy to minimize patient morbidity. We present the third documented case of a hypopharyngeal paraganglioma and the first in the English‐language literature. © 2012 Wiley Periodicals, Inc. Head Neck, 2013